2019
DOI: 10.32955/neu.istem.2019.5.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Effects Of Islamophobia On Hijab Ban Victims In Turkey In The Context Of February, 28 Hijab Ban Process And Religious Coping

Abstract: This study puts forth the state of intolerance against Muslim women wearing hijab in Turkey especially focusing on 'the process of February, 28' and establishes its significant effects on women with hijab and its development till today. Wearing hijab especially in public space has been a big problem in Turkey for the religious people in society. Although the positive developments in Turkish politics in 2008 and in 2013 which provided hijab liberty, today still Islamophobia is manifested clearly with concealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…These findings imply that embitterment is independent from all these factors, and in fact suggest that patho-mechanism of PTED stems from the violation of belief and the value system of the person, which is in line with the original description by Linden. This was actually demonstrated by previous qualitative studies where women expressed very similar narratives despite having faced the ban at different conditions and followed a different life path in terms of what they did about hijab ban (İşıker, 2011;Uysal, 2019). The dilemma of observing a religious belief or ignoring it for the sake of education, career or work seemed to be at the heart of these bitter emotions.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These findings imply that embitterment is independent from all these factors, and in fact suggest that patho-mechanism of PTED stems from the violation of belief and the value system of the person, which is in line with the original description by Linden. This was actually demonstrated by previous qualitative studies where women expressed very similar narratives despite having faced the ban at different conditions and followed a different life path in terms of what they did about hijab ban (İşıker, 2011;Uysal, 2019). The dilemma of observing a religious belief or ignoring it for the sake of education, career or work seemed to be at the heart of these bitter emotions.…”
Section: Discussionmentioning
confidence: 62%
“…Our results are supported by earlier researches, which reported significant psychological distress among the victims because of ban. In a qualitative study carried out by interviewing 10 hijab victims, all women reported to have had experienced some psychological problems as a result of the February 28th process, and some reported to have had experienced anxiety and depression (Uysal, 2019). In the above-mentioned face-to-face survey conducted on 1,112 women, although researchers did not use any validated instrument to measure psychological difficulties experienced by the participants, 9.2% of women admitted to receiving treatment for psychological problems, and actually only 3.8% said that they did not experience any psychological distress (Güveli & Kadı, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In locations with limited religious freedom, religious coping has been found to be an effective means of dealing with high-stress situations. As Uysal (2019) found, religious coping helped Turkish Muslim women overcome negative psychological trauma resulting from the hijab ban. Religious coping has also been found to be one of the means that Jewish Holocaust survivors used to process their experiences (Bettelheim 1979;Krysinska and Corveleyn 2013;Palgi et al 2011).…”
Section: Religious Copingmentioning
confidence: 99%
“…Religious coping has been studied in a variety of contexts. Religious coping is present in different faith traditions: Christianity (Pargament et al 1988(Pargament et al , 1998(Pargament et al , 2000Rosmarin et al 2009a), Judaism (Bettelheim 1979;Frei-Landau 2020;Krysinska and Corveleyn 2013;Palgi et al 2011;Pirutinsky et al 2020;Rosmarin et al 2009a, 2009b), Islam (Aguilar-Vafaie and Abiari 2007Ahmadi and Rabbani 2019;Feder et al 2013;Hasan et al 2018;Uysal 2019), and Hinduism Pulla and Woods 2016). Geographic locations of study include the United States and North America (Cacciatore and Ong 2012;Cacciatore and Thieleman 2014;Pargament et al 1988Pargament et al , 1998Pargament et al , 2000Rosmarin et al 2009aRosmarin et al , 2009b, the Middle East (Aguilar-Vafaie and Abiari 2007; Ahmadi and Rabbani 2019;Frei-Landau 2020;Mahamid and Bdier 2021;Rosmarin et al 2009b), Europe (Ahrenfeldt et al 2018;Rosmarin et al 2009b), Asia (Ahmadi and Rabbani 2019;Chow et al 2021;Feder et al 2013;Rosmarin et al 2009b;Roystonn et al 2021), and Australia (Pulla and Woods 2016).…”
Section: Religious Copingmentioning
confidence: 99%
“…Buna göre katılımcılar genel olarak dua etme, sığınma, güvenme gibi ifadelerde olumlu dini başa çıkma, üstüne gitme, düşünmeme (bastırma), hobilere yönelme gibi olumlu dini başa çıkma yöntemlerini kullanmışlardır. Başa çıkma ile yapılan araştırmalarda da genel olarak olumlu dini başa çıkmanın psikolojik açıdan pozitif etkileri olduğu tespit edilmiştir (Arıcı, 2005;Ayten et al, 2012;Baynal, 2017;Gashi, 2016;Turan, 2018;S. Uysal, 2019).…”
Section: Bu çAlışmada Imam Hatip Ortaokulunda Okuyanların Dini Konulardaunclassified